2004
DOI: 10.1159/000079284
|View full text |Cite
|
Sign up to set email alerts
|

Is the aneuploid chromosome in an apomictic <i>Boechera holboellii</i> a genuine B chromosome?

Abstract: The Boechera holboellii complex comprises B. holboellii and B. drummondii, both of which can reproduce through sex or apomixis. Sexuality is associated with diploidy, whereas apomictic individuals can either be diploid, aneuploid or triploid. Aneuploid individuals are found in geographically and genetically distinct populations and contain a single extra chromosome. It is unknown whether the supernumerary chromosomes are shared by common descent (single origin) or have originated via introgressive hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 33 publications
(61 reference statements)
2
50
0
Order By: Relevance
“…com.). Aneuploidy was reported in the B. holboellii species complex (Bo¨cher 1951, Roy 1995, Sharbel and Mitchell-Olds 2001, and recent studies involving DNA sequences of microsatellites markers (Sharbel et al 2004) suggest that aneuploidy involves non-recombining B chromosomes that may also play a role in apomixis.…”
Section: Problematic Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…com.). Aneuploidy was reported in the B. holboellii species complex (Bo¨cher 1951, Roy 1995, Sharbel and Mitchell-Olds 2001, and recent studies involving DNA sequences of microsatellites markers (Sharbel et al 2004) suggest that aneuploidy involves non-recombining B chromosomes that may also play a role in apomixis.…”
Section: Problematic Groupsmentioning
confidence: 99%
“…, 2004aDobesě t al. , 2004bKoch et al 2003c;Sharbel et al 2004) Windham et al (2004), the first serious problem in the study of Boechera is taxon identity, and erroneous determinations in the holdings of the major herbaria can be as high as 40%. Hybridization appears to have played a far more major role in the evolution of the genus than was suggested by Rollins (1983) and Mulligan (1996).…”
Section: Problematic Groupsmentioning
confidence: 99%
“…Heterochromatic chromosomes (Het) and supernumary heterochromatic-B chromosomes have been detected in asexually reproducing (apomictic) Boechera lines (Sharbel et al, 2004;Kantama, 2005;Sharbel et al, 2005). The Het chromosome is derived from B. stricta as based on hybridization of pericentromeric repeats (Kantama, 2005;Schranz et al, 2006a) and genetic analysis has demonstrated that the Het chromosome can be crossed into B. stricta without conferring a dominant apomictic phenotype (Schranz et al, 2006a).…”
Section: Recombination Suppression Of Bstlg1mentioning
confidence: 99%
“…Numerous studies have analyzed molecular and phenotypic diversity of Boechera species. This includes the molecular evolutionary analysis of gene families (Bishop et al, 2000;Schein et al, 2004;Benderoth et al, 2006), the phylogeography of haplotypes (Dobeš et al, 2004b;Song et al, 2006), the occurrence of supernumary B chromosomes (Böcher, 1951;Sharbel et al, 2004), variation in breeding systems and ploidy (Sharbel and MitchellOlds, 2001;Schranz et al, 2005;Schranz et al, 2006a), drought tolerance (Knight et al, 2006), morphological and taxonomical diversity (Rollins, 1993;Al-Shehbaz, 2003;Windham and Al-Shehbaz, 2006), and the evolved responses to pathogen or insect pests (Roy, 1993;Roy and Kirchner, 2000;Jones et al, 2006). The further elucidation of these and other patterns of variation would be greatly aided by the creation and analysis of segregating genetic stocks.…”
mentioning
confidence: 99%
“…The extra chromosomes recorded in our study may be B chromosomes as they varied in number (0-1) between and within populations, which is a characteristic of this type of chromosome. B chromosomes are not essential for the organism, are often heterochromatic and rich in repetitive sequences (Sharbel et al 2004), features, however, which we have not yet established. In the numerous chromosome counts for V. officinalis aneuploidy is never mentioned (Titz 1964, 1969, Titz & Titz 1979, 1981, and one could suppose that the occurrence of aneuploidy is relatively rare.…”
Section: Frequencies Of Cytotypes Of Deviant Ploidy and Of Aneuploidsmentioning
confidence: 81%